Toward Achieving Latino Food Equity: Insights from Latino Community Leaders in Central Eastern Washington - Grijalva-Martinez, Evelyn Isabel (My University, 2025)
Latino Food Equity acknowledges the diverse cultural and socioeconomic factors that influence food access and consumption within the Latino community, promoting more inclusive and effective strategies to achieve food equity. This is a qualitative sub-study of the Food Research and Equity Collaborative (FrEsCo), and it aims to document the perception of community leaders in Central Eastern Washington on the role of their community-based organization in advancing Latino food equity. Twelve key informant, semi-structured interviews were conducted with diverse community leaders and representatives of organizations working towards Latino food equity in the region, and the data were coded following the six steps of thematic analysis. The following four themes were identified: 1) The context in which community leaders and organizations operate, 2) Accessing food and resources for the Latino community is challenging, 3) Enhancing equitable access to food and resources for the Latino community, and 4) Opportunities and strengths of community-based organizations and the Latino community in Central Eastern Washington to advance Latino food equity. The findings reveal that addressing the lack of food access extends beyond food assistance, touching on many more factors including social, economic, legal, and geographical considerations. Community leaders highlighted the necessity for equal opportunities and respect for all Latinos. Overall, this study offers valuable insights into the complexities of addressing Latino food equity which could inform the development of tailored interventions and policies.
Thesis (Master's)--University of Washington, 2025
Keywords: Community Based Participatory Research; Community Leaders; Food Access; Food Insecurity; Latino Food Equity; Nutrition; Public health; Nutritional sciences